Masking the Identities of Celebrities and Personally Familiar Individuals: Effects on Visual and Auditory Recognition Performance. (October 2017) - Krix, Alana C.; Sauerland, Melanie; Schreuder, Maartje J.
The current study compared the effectiveness of masking on recognition performance for faces and voices of celebrities and personally familiar individuals. On the basis of the theory suggesting stronger memory representations for personally familiar individuals, we expected masking to be more effective for celebrities than for personally familiar stimulus persons. Furthermore, we sought to replicate the face recognition advantage with masked stimuli. Face pixelation and electronic changes of the voice pitch were applied as masking techniques, using four masking levels for each stimulus. Thirty-one undergraduate students were presented with the masked faces and voices of 10 celebrities and 10 personally familiar fellow students. As expected, more correct recognitions occurred for faces than for voices, suggesting that masking does not counteract the mechanisms causing the face recognition advantage. Unexpectedly, masking effectiveness did not differ between celebrities and personally familiar individuals. This may be due to the type of personally familiar individuals used. Within personally familiar stimuli, increased familiarity did not predict the effectiveness of masking. Whereas the highest masking level eliminated speaker recognition, masking did not fully eliminate face recognition. From a practical perspective, the findings especially question the suitability of pixelation as a means for identity concealment.